Implementation of Restorative Justice as a Criminal Policy: A Literature Review - Irwan Soeharlim; Regina Yura Fitriah Sari; Ani Wahyuni; Oky Rona Wijaya; Ahmad Fahrul Rozi; Mustofa Kamil (Universitas Islam Negeri Raden Mas Said Surakarta, 2026)
This literature review examines the implementation of restorative justice as a contemporary criminal policy instrument, tracing its paradigmatic shift from retributive punishment to relational healing. Drawing on scholarly literature published between 2020 and 2026, the study synthesizes conceptual foundations, regulatory frameworks, operational mechanisms, and implementation barriers. Findings reveal that while Indonesia has advanced restorative practices through sectoral regulations and juvenile diversion, fragmented legislation, resource constraints, and entrenched retributive cultures hinder consistent application. Evidence indicates that properly facilitated processes enhance victim satisfaction, reduce judicial burdens, and promote offender accountability, yet success depends on voluntary participation and institutional safeguards. The review concludes that realizing restorative justice’s potential requires unified legislation, sustained capacity building, and systematic monitoring. Ultimately, it offers a culturally resonant pathway toward humane criminal justice reform.